Cytogenomic characterization of Euschistus (Heteroptera: Pentatomidae) species and strains reveals low chromosomal and repetitive DNAs divergences - Hickmann, Frederico; Soares Corrêa, Alberto; Bardella, Vanessa B [UNESP]; Milani, Diogo [UNESP]; Clarindo, Wellington R; Soares, Fernanda A. F; Carvalho, Renata F; Mondin, Mateus; Cabral-De-Mello, Diogo C [UNESP] (My University, 2023)
Euschistus stink bugs are important pests on soybean crops, including the Neotropical representatives Euschistus heros, Euschistus crenator, and Euschistus taurulus. Despite their importance, little genomic and chromosomal information is available. Genomic and chromosomal differences can play an important role in establishing reproductive barriers between species and populations. Here we investigate the chromosomes, some repetitive DNAs, and genome sizes of three Euschistus species, including two E. heros strains (North strain-NS and South strain-SS), to address chromosomal evolution and genomic differentiation. Our data reveal conservative karyotypes and only one possible inversion among Euschistus species. Moreover, we observe Y chromosome reorganization through differential microsatellite accumulation. The nuclear genome sizes are slightly variable among species. We noticed a differential accumulation of satellite DNAs, mainly on the Y chromosome, in the two strains of E. heros. Although typical meiotic behaviour, demonstrating full compatibility, was observed in hybrids despite interference on chiasmata frequency. This data shows that chromosomal and repetitive DNAs do not prevent secondary contact between E. heros strains, contributing to genetic variability in hybrids. Therefore, we provide data about Euschistus pests and their chromosomal characteristics, representing the first step in understanding their genomic organization and evolution.
Keywords: allopatric strains; genome size; hybridization; inversion; karyotype; repetitive DNA; satDNA; soybean pest; speciation; stink bugs